“Inconsistency between words and deeds”: a meta-analysis of the moderating and mediating mechanisms of bridging the exercise-intentional-behavior gap - Yang, Zexin; Li, Jun; Liu, Xiaoming (Frontiers in Psychology, 2025)
Exercise intention is a crucial predictor of exercise behavior; however, the existence of the “intention-behavior gap” is an undeniable fact, and the strength and mechanisms of their relationship remain controversial. This study, based on 92 empirical studies (109 independent samples, 47,548 participants), employs meta-analysis to examine the relationship strength between exercise intention and behavior, the moderating effects of participant characteristics, and the mediating role of planning and action control. The findings are as follows: (1) the relationship strength between exercise intention and behavior is moderate (r = 0.41); (2) the moderating effects of age, educational stage, health status, socioeconomic status, cultural background, and economic level are significant, except for gender; (3) action planning, coping planning, and action control mediate the relationship between exercise intention and behavior in a chain-like manner, with action control (Single mediation effect was 13.45%) being the closest predictor of behavior. This undoubtedly provides inspiration for the formulation of intervention strategies. Strengthening action control as the core target, supplemented by action plans and coping plans can better promote the implementation of exercise behavior. Future research is recommended to strictly control participant characteristics, conduct long-term longitudinal tracking and experimental interventions, strengthen the use of objective measurement tools, and explore and analyze new theories and variables to facilitate the translation of exercise intention into behavior.